The effect of airflow rates and aeration mode on the respiration activity of four organic wastes: Implications on the composting process. (July 2017) - Mejias, Laura; Komilis, Dimitrios; Gea, Teresa; Sánchez, Antoni
Highlights: The effect of various air flowrates and two aeration modes was tested on four wastes. Beyond a threshold air flowrate, all measured dynamic indices were similar. These threshold aeration values ranged from 42 to 77 NL air kg −1  DM h −1 . No statistical differences existed between the two operating aeration modes. The DRI24 ranged from 2 to 6 g O2 kg −1  DM h −1 . Abstract: The aim of this study was to assess the effect of the airflow and of the aeration mode on the composting process of non-urban organic wastes that are found in large quantities worldwide, namely: (i) a fresh, non-digested, sewage sludge (FSS), (ii) an anaerobically digested sewage sludge (ADSS), (iii) cow manure (CM) and (iv) pig sludge (PS). This assessment was done using respirometric indices. Two aeration modes were tested, namely: (a) a constant air flowrate set at three different initial fixed airflow rates, and (b) an oxygen uptake rate (OUR)-controlled airflow rate. The four wastes displayed the same behaviour namely a limited biological activity at low aeration, while, beyond a threshold value, the increase of the airflow did not significantly increase the dynamic respiration indices (DRI1 max, DRI24 max and AT4 ). The threshold airflow rate varied among wastes and ranged from 42 NL air kg −1  DM h −1 for CM and from 67 to 77 NL air kg −1  DM h −1 for FSS, ADSS and PS. Comparing the two aeration modes tested (constant air flow, OUR controlled air flow), no statistically significant differences were calculated between the respiration activity indices obtained at those two aeration modes. The results can be considered representative for urban and non-urban organic wastes and establish a general procedure to measure the respiration activity without limitations by airflow. This will permit other researchers to provide consistent results during the measurement of the respiration activity. Results indicate that high airflows are not required to establish the maximum respiration activity. This can result in energy savings and the prevention of off-gas treatment problems due to the excessive aeration rate in full scale composting plants.